2014
DOI: 10.1002/pc.23056
|View full text |Cite
|
Sign up to set email alerts
|

Novel interpenetrating amphiphilic Co‐networks based on compatibilized NBR/SBR‐montmorillonite composites: A study on the oil absorption characteristics

Abstract: This work explores the fabrication of novel amphiphilic interpenetrating co‐network structures that may afford a reasonable solution to the problem of oil spills. It depends upon compatibilization of the binary immiscible rubber blend, containing the polar acrylonitrile–butadiene rubber and the non‐polar styrene–butadiene rubber. The compatibilization process was accomplished successfully using organic‐inorganic hybrid structures based on montmorillonites, priory treated with a hydrophobic cationic agent to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…This may be due to the high polarity of NBR rubber which causes rubber chains to be attached to mSF particle, leading to more smooth and homogeneous surfaces than unmodified silica fume and commercial silica. This means that, the surface treatment of SF with R1 helped in improving the dispersion in the rubber matrix, these behaviors were confirmed with that obtained by Essawy et al (2014b, 2015).…”
Section: Scanning Electron Microscopy Morphologysupporting
confidence: 81%
“…This may be due to the high polarity of NBR rubber which causes rubber chains to be attached to mSF particle, leading to more smooth and homogeneous surfaces than unmodified silica fume and commercial silica. This means that, the surface treatment of SF with R1 helped in improving the dispersion in the rubber matrix, these behaviors were confirmed with that obtained by Essawy et al (2014b, 2015).…”
Section: Scanning Electron Microscopy Morphologysupporting
confidence: 81%
“…In addition, the contact angle 43 (the angle formed by the intersection of the oil-water interface) gives a better idea about the wettability of the sorption surface. Small contact angles (80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90) correspond to high wettability, when the liquid spreads on the surface. Similarly, large contact angles (140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150) correspond to low wettability, when the liquid beads on the surface.…”
Section: Principles Of Oil In Water Separationmentioning
confidence: 99%
“…Essawy et al 87 reported a novel interpenetrating amphiphilic co‐networks based on compatibilized acrylonitrile butadiene rubber/styrene butadiene rubber (NBR/SBR) montmorillonite composites provide a possible solution to oil spills problems. The polymer network consists of polar acrylonitrile butadiene rubber and the non‐polar styrene butadiene rubber and the compatibilization were accomplished by montmorillonite.…”
Section: Organic Polymer Nanocomposite Sorbentsmentioning
confidence: 99%
“…This leads to more free volume in the copolymer network and consequently; more water can be absorbed (20) . This can be attributed to the presence of the pores inside the formulation (21) .…”
Section: Swelling Propertiesmentioning
confidence: 99%